Effectiveness of Structured Training Programme Regarding Adult Basic Life Support on Knowledge of Nurses` in Zoba Maekel and National Referral Hospitals, Eritrea, 2018 - Ghirmai, Filmon Abraham; Weldeghiorgis, Ghidey Ghebreyowhanness; Bahlebi, Teklu Tsegay; Tesfamariam, Eyasu Habte (Archives of Clinical and Medical Case Reports, 2022)
Background: In Eritrea nurses provide most of the health care in the primary, secondary and tertiary level health facilities. The rate of trauma and medical emergencies are on the increase so nurses should have adequate and updated knowledge on Basic Life Support in order to be able to implement effective interventions in cardiac arrest situations. Aim: The objective of this study was to assess the effectiveness of structured training programme regarding Adult Basic Life Support on knowledge of nurses. Method: A quasi-experimental single group, pretest-posttest and retest design was utilized. Forty (40) nurses’ participated in the study. Structured and modified questionnaire was used to collect data. Data were analyzed using the Statistical Package for Social Sciences (SPSS) Version 22.0 program. Frequencies, percentages, mean and standard deviation was used to describe the data. One way repeated measures of ANOVA was used to check the possible change in knowledge of the nurses at preintervention, immediate and three months’ after intervention. A p-value < 0.05 was considered to be statistically significant. Results: The findings showed an acquisition of Adult Basic Life Support knowledge among the study participants following a four hour Basic Life Support training programme. Before training, the mean score of the study participant on knowledge questions was 9.58/20 and none of the respondents got a pass mark. Immediately after the training the mean score of the study participants was increased to 15.9/20 and 55.0% of the study participant got a passing mark. Significant deterioration from the immediate training score was found three months following Basic Life Support training as score was decreased to 14.9 and 40% of the respondents got a pass